Regulations On Proofing Marriage Announcement As A Requirement For Catholic Divorce In Indonesia - Zamiatun, Arda; Rachmi Sulistyarini; Nur Chanifah (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study examines the urgency of the annulment letter in the Catholic divorce system in Indonesia as a legal instrument that plays a crucial role in bridging the gap between civil law and the canon law of the Catholic Church. The annulment letter serves not only as an administrative document but also as proof of the legality of the annulment of marriage, determining the validity of the marriage sacrament according to Church law. This study found that the lack of clear regulations regarding the recognition and verification of annulment letters in district courts can lead to legal uncertainty and conflict over the dual status between civil and canonical recognition. The annulment process in the Catholic Church itself is a pastoral judicial mechanism that assesses the validity of a marriage based on the norms of faith and canon law, with stages including filing, examining evidence, and a tribunal decision. This study emphasizes the importance of synchronizing the results of the ecclesiastical tribunal process with the national legal system to ensure justice, legal certainty, and the protection of the rights of Catholics. A comparative approach to the legal systems of other countries shows that the integration of the results of religious tribunal decisions into the national legal system can be achieved through transparent and measurable administrative mechanisms. Thus, the regulation of proof and recognition of annulment letters in Indonesian national law is expected to realize harmonization between religious law and state law, while strengthening legal, spiritual, and social protection for Catholic couples.